The impact of resveratrol on ocular microcirculation and structural changes in an experimental model of ischemia-reperfusion of the retina - T. N. Kiseleva; A. V. Chudin; A. I. Shchipanova; I. P. Khoroshilova-Maslova (Российский офтальмологический журнал, 2018)
Purpose. To study the effect of antioxidant resveratrol on hemodynamics and morphological changes in the ocular structure of rats with retinal ischemia-reperfusion injury. Material and Methods. The experimental study was performed on 50 Wistar rats. The animals were divided into two groups: group I (20 intact animals) and, group II (30 animals who received resveratrol per os for one month. We modeled unilateral ischemia-reperfusion of the eye by increasing IOP to the level of 110 mm Hg within 30 minutes, pumping air into the anterior chamber. Group I was further divided into subgroup IA (10 animals undergoing ischemia-reperfusion modeling of one eye and IB (control) which consisted of 10 intact rats. All animals of group II kept receiving resveratrol for 1 month and underwent the modeling of ischemia-reperfusion of the eye, whereupon the administration of reservatrol was resumed for another month. Ocular blood flow was estimated using power Doppler (PD) and pulsed-wave spectral Doppler ultrasonography before ischemia-reperfusion and 3, 7, 30 days after it. The eyeball was enucleated on the 3 rd, 7th, or 30 th day in the post-ischemic period of the experiment to enable a pathomorphological study. Results. The signs of ischemic damage of the anterior and posterior segments of the eye were reduced in rats who received resveratrol during the pre-ischemic (within 30 days) and the post-ischemic follow up period (30 days). We noted a statistically significant increase of peak systolic velocity (Vsyst), increase of end diastolic velocity (Vdiast) and decreased resistance index (RI) in the central retinal artery and short posterior ciliary arteries of rats that were treated with resveratrol as compared to the respective values found in rats with ischemia-reperfusion of the retina who were not given resveratrol. A histopathological examination revealed areas with intact retinal layers in rats who received resveratrol for a long period (1-2 months). Conclusions. An improvement of ocular blood flow and a neuroprotective effect was found in rats with ischemia-reperfusion who received resveratrol // Russian Ophthalmological Journal, 2016; 3: 66-74. doi: 10.21516/2072-0076-2016-9-3-66-74.